Phytoremediation Technique to Herbicides-Polluted Soils - Paiva, Maria Carolina Gomes; Mendes, Kassio Ferreira (Pesticides in Agriculture and Environment, 2021)
The use of pesticides is an indispensable practice in technical agriculture, avoiding the reduction in crop productivity and increasing the quality of the final product. Pesticides can be divided into different classes, among which one can mention herbicides, fungicides, acaricides and insecticides. Herbicides are the most widely used pesticide class on a large scale and are efficient tools in weed control, and have low cost compared to other control methods and reduce labor dependence (RAMBORGER et al., 2017). Some herbicides have a long residual effect, which allows weed control for a longer period, thereby reducing the number of applications (PROCOPIO et al., 2009a). However, the presence of the herbicide in the soil for a prolonged period can cause damage to susceptible crops (carryover) in rotation/succession systems, negatively impact non-target organisms, especially beneficial soil microorganisms, in addition to raising the risks of leaching and contamination of soils and surface and groundwater (VIEIRA et al., 2007; DAN et al., 2012; LANE et al., 2012; OTTO et al., 2012; SILVA et al., 2014). Thus, as a form of decontamination of soils submitted to herbicide applications, the development of bioremediation strategies is being demanded, reducing environmental and agronomic impacts.